Discussion on Monitoring Methods for the Temperature Difference Between Upper and Lower Layers of Mass Concrete - HUANG Yao-ying, FU Yu-chen, ZHUANG Wei, TU Yue-tong, HU Yu (长江科学院院报)
[Objectives] When constructing concrete hydraulic projects in cold and high-altitude regions, or when promoting interconnection of water networks through the construction of concrete-based backbone projects such as sluices, ship locks, and pumping stations, long intervals in concrete pouring are inevitable, and the temperature difference between the upper and lower layers of concrete becomes a key concern. Although the upper-lower temperature difference, the allowable foundation temperature difference, and the internal-external temperature difference are three important temperature control indicators in the thermal control and crack prevention of mass concrete, the vague or overly theoretical definition of the upper-lower temperature difference makes its calculation inconvenient and monitoring difficult to implement effectively, making it hard to apply this indicator in actual construction. Therefore, effectively addressing the calculation and monitoring of the temperature difference between the upper and lower layers of concrete is of urgent engineering significance. [Methods] Based on existing definitions of the temperature difference between the upper and lower layers and considering the operability of monitoring, this study proposed four calculation methods following the principle of matching “calculation method-monitoring index”. These methods are based respectively on the “temperature within the geometric vertical centerline range” and the “temperature within the overall influence range” of the upper and lower pouring segments. Through simulating the temperature field and creep stress field of mass concrete with different interval durations, samples of maximum tensile stress in concrete and samples of upper-lower temperature differences under different interval conditions were obtained. Subsequently, statistical tests were conducted on the above samples to derive the corresponding probability density distribution functions of the maximum tensile stress and temperature difference between upper and lower layers. Then, the failure probability of the maximum tensile stress was determined based on the allowable tensile stress of concrete. Finally, assuming that the failure probabilities of the maximum tensile stress and temperature difference between upper and lower layers were equal, the allowable temperature differences between the upper and lower layers of concrete corresponding to the four calculation methods were proposed. [Results] Based on the concrete pouring of the bottom slab-guide angle section of a large ship lock, simulation calculations of the temperature field and creep stress field of mass concrete were carried out for different seasons (spring, summer, autumn, and winter) and various interval durations (30 to 180 days). According to the proposed method for determining the allowable temperature difference between upper and lower layers, four allowable temperature differences were derived: 29.14 ℃, 19.95 ℃, 20.29 ℃, and 18.02 ℃, respectively. These values showed some deviations from the currently recommended range of 15-20 ℃ in existing standards. [Conclusions] Because the calculation methods correspond to their respective monitoring indicators, different approaches to calculating the temperature difference between the upper and lower layers result in significant differences in the allowable temperature differences. Considering the operability of on-site monitoring, it is recommended to use the calculation method based on the “temperature within the geometric vertical centerline range of the upper and lower pouring segments” and its corresponding monitoring indicator to monitor the temperature difference between upper and lower layers of mass concrete on site.